2014
DOI: 10.1080/23279095.2013.860604
|View full text |Cite
|
Sign up to set email alerts
|

Limited Knowledge of Concussion Symptoms in College Athletes

Abstract: Concussions are common in athletes and often go unreported. A likely contributor to underreporting of concussions in athletes is lack of knowledge of concussion-related symptoms. The current study assessed concussion symptom knowledge in 382 Division I athletes and 230 nonathletes. Participants were asked to identify potential symptoms following a concussion from a list of both real symptoms and distractors. Student-athletes expected significantly more total symptoms following a concussion than did nonathletes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 17 publications
4
31
1
Order By: Relevance
“…Indeed, athletes are known to suppress symptom reports as they may be unaware they are related to concussion, or they have a strong desire to return to play prior to recovery [18, 34, 41, 44, 55]. In addition, the media has reported on athletes intentionally performing poorly on baseline assessments [33] to mask postconcussion deficits, and the reliability of both neurocognitive and postural control assessments may be less than optimal for clinical purposes [5, 9, 49, 53].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, athletes are known to suppress symptom reports as they may be unaware they are related to concussion, or they have a strong desire to return to play prior to recovery [18, 34, 41, 44, 55]. In addition, the media has reported on athletes intentionally performing poorly on baseline assessments [33] to mask postconcussion deficits, and the reliability of both neurocognitive and postural control assessments may be less than optimal for clinical purposes [5, 9, 49, 53].…”
Section: Introductionmentioning
confidence: 99%
“…For example, anecdotal accounts suggest that some athletes may inflate baseline symptom reports to mask elevated postinjury scores. Others may not recognize concussive signs and symptoms or intentionally not report them once the injury occurs [30][31][32][33] because of influence from teammates, friends, coaches, or parents. Furthermore, some athletes may be motivated to inflate symptom reports or continue reporting symptoms despite injury resolution as a means to leave a sport.…”
Section: The Symptom Evaluationmentioning
confidence: 99%
“…Physical signs and symptoms include headaches, visual disturbances, and fatigue; cognitive signs and symptoms include memory loss and attention difficulties, and behavioral signs and symptoms include depression and changes in mood [1,[7][8][9][10]. Behavioral and cognitive concussion symptoms are less commonly recognized than physical symptoms [11][12][13][14]. Serious long-term health effects that have been found in athletes with a history of concussions include long-term cognitive deficits, dementia, depression, and chronic traumatic encephalopathy [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The vulnerability of youth to the effects of concussion give rise to the need for concussion education and awareness among student athletes. Despite increased efforts in this area, studies have demonstrated deficits in student-athletes' knowledge of concussion symptoms, especially behavioral symptoms [11][12][13]22].…”
Section: Introductionmentioning
confidence: 99%